Comparison of Local and Systemic DTPA Treatment Efficacy According to Actinide Physicochemical Properties Following Lung or Wound Contamination in the Rat - Griffiths, Nina M.; Van der Meeren, Anne; Grémy, Olivier (Frontiers in Pharmacology, 2021)
Purpose: In cases of accidents in nuclear facilities or subsequent to terrorist activities, the most likely routes of internal contamination with alpha-particle emitting actinides, such as plutonium and americium are by inhalation or following wounding. The treatment remit following internal contamination is to decrease retention and in consequence potential health risks. The only approved drug for decorporation of Pu and Am is diethylenetriaminepentaacetic acid that has limited efficacy following contamination with insoluble actinides, irrespective of the contamination route. The objectives of this work were to evaluate the efficacy of prompt local and/or systemic DTPA treatment regimens following lung or wound contamination with insoluble or moderately soluble actinides. The conclusions are drawn from retrospective analysis of experimental studies carried out over 10 years. Materials and Methods: Rat lungs or wounds were contaminated either with poorly soluble Mixed OXide (U,Pu O2) or more soluble forms of Pu (nitrate or citrate). DTPA treatment was administered promptly after contamination, locally to lungs or directly into the wound site. Intravenous injections of DTPA were given either once, repeated or in combination with the local treatment. Doses ranged from 1 to 30µmol/kg. Animals were euthanized from day 7 to 21 and urine and tissue activity measured for determination of decorporation efficacy. Results: Different experiments confirmed that whatever the route of contamination, most of the activity is retained at the entry site after insoluble MOX contamination as compared with more soluble forms resulting in very low activities reaching the systemic compartment. DTPA treatment regimens showed no better than a 13% reduction in lung or wound levels compared with untreated animals. However, in all cases systemic retention (skeleton and liver) was reduced and urinary excretion enhanced irrespective of the contamination route or DTPA treatment regimen. Conclusion: The present study demonstrates that despite limitation of retention in systemic organs, different DTPA protocols were ineffective in removing insoluble actinides deposited in lungs or wound site. For moderately soluble actinides, local or intravenous DTPA treatment reduced activity levels both at contamination and systemic sites. However, whatever the DTPA protocol or the actinide form, the reduction factor in retention organs is similar.